Analisis Pengaruh Perlakuan Alkali Terhadap Wettability Serat Tunggal Widuri - Dominggus Adoe; Yeremias M. Pell; Beni Sanak (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2021)
Along with its development, composites do not only use synthetic fibers, but there are already composite reinforcing materials made from natural fibers. The advantages of natural fiber as a reinforcing material for composite materials are: the ratio between strength and density is quite high, corrosion resistance, low cost and easy manufacturing process. The use of natural fibers as reinforcement for polymer materials provides opportunities for some natural fibers to be used as reinforcement for polymer composites, one of which is thistle fiber. The treatment used was alkaline treatment (NaOH) with percentages of 2%, 3%, 4%, 5%, 6%, and 7%, respectively, and the soaking time of 30, 60, 90, 120 minutes, and fiber. Widuri bark without treatment as a comparison. The purpose of this study was to determine the effect of the concentration of alkaline solution and the duration of immersion on the wettability of single widuri fibers. Single fiber testing refers to ASTM D3379 standard. From the results of the fiber contact angle test with 6% NaOH treatment for 120 minutes with a cos price of 0.906725322 with a droplet geometry that tends to be barrel. Meanwhile, fiber treated with 3% NaOH for 60 minutes had the lowest cos value of 0.472037963 with a droplet geometry that tends to be clam-shell